Perkembangan Kajian mengenai Pendidikan Islam dan AI: Telaah Analisis Bibliometrik Riset terhadap Publikasinya Tahun 2000-2025 - Huda, Ali Anhar Syi'bul; Aghnia, Aghnia; Hamdi , Hamdi; Ahmad , Walid In’am; Anugerah, Dena Sri (SENTRI: Jurnal Riset Ilmiah, 2025)
This research was prompted by the growing interest in the integration of Islamic education and artificial intelligence (AI) from 2000 to 2025. The aim of this study is to map the development of publications, sources, researchers, and research topics, as well as to identify issues that have the potential for future development. The research design is quantitative with a bibliometric research method. Data collection was conducted in September 2025 using primary data from 903 publications in Crossref, supported by secondary data in the form of books, proceedings, and papers. The Publish or Perish (PoP) and VOSviewer applications were used as analysis tools, while data interpretation was carried out descriptively and qualitatively by the researcher. The results show a surge in publications since 2020, with a peak of 129 articles in 2025. The sources of publications were dominated by scientific journals (880), proceedings (13), and OSF (10). A total of 1,134 researchers were involved, with 9 lead authors each publishing 4 publications. Emerging topics included Islamic teaching, noble character, educational goals, collaboration, and artificial intelligence ethics, while potential issues included beliefs, diversity, philosophy, modernisation, and evaluation. The limitations of this study are the use of simple analytical tools and the lack of coverage of international databases such as Scopus/WoS. Recommendations for future research include more comprehensive studies with the integration of bibliometric analysis and empirical studies.